Interactions between inferential strategies and belief bias. - Markovits, Henry; Brisson, Janie; Chantal, Pier-Luc; Thompson, Valerie (Memory & Cognition, 2017)
The dual strategy model of reasoning proposed by Verschueren, Schaeken, and d'Ydewalle ( Thinking & Reasoning, 11(3), 239-278, 2005a; Memory & Cognition, 33(1), 107-119, 2005b) suggests that people can use either a statistical or a counterexample-based strategy to make deductive inferences. Subsequent studies have supported this distinction and investigated some properties of the two strategies. In the following, we examine the further hypothesis that reasoners using statistical strategies should be more vulnerable to the effects of conclusion belief. In each of three studies, participants were given abstract problems used to determine strategy use and three different forms of syllogism with believable and unbelievable conclusions. Responses, response times, and feeling of rightness (FOR) measures were taken. The results show that participants using a statistical strategy were more prone to the effects of conclusion belief across all three forms of reasoning. In addition, statistical reasoners took less time to make inferences than did counterexample reasoners. Patterns of variation in response times and FOR ratings between believable and unbelievable conclusions were very similar for both strategies, indicating that both statistical and counterexample reasoners were aware of conflict between conclusion belief and premise-based reasoning.